Conformity, Self-Esteem, and Psychological Well-Being in Adolescents with Body Dysmorphic Disorder Tendencies - Bertha Elinda; Arthur Huwae (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to determine the relationship between conformity, self-esteem, and psychological well-being in adolescents who experience body dysmorphic disorder tendencies. The method used is multiple correlational and bivariate cross-sectional quantitative research. The participants of this study were 315 adolescents who experienced body dysmorphic disorder tendencies using a proportional stratified random sampling technique. Measurements used The Conformity Scale (α = 0.865), Rosenberg Self-Esteem Scale (α = 0.832), and Ryff Psychological Well-Being Scale (α = 0.936). The results prove that conformity and self-esteem are jointly related to psychological well-being in adolescents who experience body dysmorphic disorder tendencies (F change = 44.496 with sig. = 0.000; p<0.05). Partially, conformity is negatively related to psychological well-being (r = -0.178 with sig. = 0.001; p<0.01), and self-esteem is positively associated with psychological well-being (r = 0.426 with sig. = 0.000; p<0.01). These results indicate that conformity and self-esteem are factors associated with increased or decreased psychological well-being in adolescents who experience body dysmorphic disorder tendencies. Keywords: conformity, self-esteem, psychological well-being, adolescents, body dysmorphic disorder